Working with adult abuse : a training manual for people working with vulnerable adults - Pritchard, Jacki (JKP resource materials., 2007)
Working with Adult Abuse is a comprehensive manual for trainers of those working with vulnerable adults. The author covers all aspects of adult abuse cases, from the recognition of adult abuse, whether in the community or within an institution, through to the investigation, case conference and risk assessment stages. Practical advice is presented within the historical context of adult abuse policy, and is complemented by specialised chapters on the abuse of specific sections of society, such as older people, younger adults and black and minority ethnic people. For use across all disciplines, e.